Desenvolvimento de nanopartículas de quitosana para adminstração nasal de zidovudina - Barbi, Mariana da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Zidovudine (AZT) is the drug most commonly used in AIDS treatment, isolated or in combination with other antiretroviral agents, but it has certain limitations due to its therapeutic dose-dependent haematological toxicity. In addition, it has low oral bioavailability, since it undergoes pre-systemic metabolism. The nasal route has been used as an alternative route for drug administration, because it can promote its direct absorption to blood circulation, avoiding hepatic metabolism. However, this route presents as a factor limiting the mucociliary clearance mechanisms that remove quickly the formulation of the nasal cavity. To prolong the residence time of formulations, in this direction, has been proposed the development of mucoadhesive systems. Among the various existing systems, the use of chitosan (QS), as mucoadhesive polymer, has been widely exploited in the preparation of nanoparticles (NPs). The objective of this study was to develop and characterize QS’s NPs for intranasal administration of AZT. For both NPs have been developed by ionic crosslinking of QS with sodium tripolyphosphate (TPP). These NPs were characterized by studies of particle size distribution, zeta potential, morphology, mucoadhesion tests, assessing the ability of encapsulation of the drug and permeation profile of AZT. The evaluation of AZT in the NPs was determined by UV-Vis spectroscopy. Mucoadhesion measures were made using a texture analyzer, using a mucin disk and porcine mucous membrane , and permeation assay were conducted using porcine nasal mucous membrane adapted to the Franz cell. These results suggest that the systems in hand have great potential for nasal AZT administration

A zidovudina (AZT) é o fármaco mais utilizado no tratamento da AIDS, sozinho ou em combinação com outros anti-retrovirais, porém possui certa limitação terapêutica devido a sua toxicidade hematológica dose-dependente. Além disso, apresenta baixa biodisponibilidade oral, pois sofre metabolismo pré-sistêmico. A via nasal tem sido muito utilizada como rota alternativa para administração de fármacos, pois pode promover sua absorção direta para circulação sanguínea, evitando o metabolismo hepático. Entretanto, esta via apresenta como fator limitante os mecanismos de depuração mucociliar que removem rapidamente a formulação da cavidade nasal. Para prolongar o tempo de permanência das formulações nesta via, tem sido proposto o desenvolvimento de sistemas mucoadesivos. Dentre os vários sistemas existentes, a utilização da quitosana (QS), como polímero mucoadesivo, tem sido muito explorado na preparação de nanopartículas (NPs). O objetivo deste trabalho foi desenvolver e caracterizar NPs de QS para administração intranasal do AZT. Para tanto foram desenvolvidas NPs de QS através do método de gelificação ionotrópica com tripolifosfato de sódio. Estas NPs foram caracterizadas por determinação da distribuição granulométrica, potencial zeta, morfologia, ensaios de mucoadesão, avaliação da capacidade de encapsulação do fármaco e do perfil de permeação do AZT. A avaliação da incorporação do AZT nas NPs foi determinada por espectroscopia UV-Vis. As medidas de mucoadesão foram realizadas através de um analisador de textura, utilizando disco de mucina e uma mucosa suína; e os ensaios de permeação foram realizados utilizando mucosa nasal suína adaptada à célula de Franz. Estes resultados sugerem que estes sistemas possuem grande potencial para administração nasal do AZT
Keywords: Nanopartículas; Quitosana; Aids; Sistema de liberação de fármacos; Zidovudiva; Aids and Zidovudive; Nanoparticles